Differences in organization citizenship behavior between "serumpun" countries (Indonesia – Malaysia). Issue 3 (8th July 2019) - Suharnomo, Suharnomo; Hashim, Fathyah
Abstract : Purpose: This paper aims to examine the effect of job motivation and commitment on organizational citizenship behavior (OCB) of Indonesian and Malaysian employees. Organizational and national cultures are introduced as moderators and OCB as a mediator to investigate their relationships in the context of job performance. Design/methodology/approach: The sample was drawn from employees using a purposive sampling method. A total of 264 valid questionnaires were obtained from employees. The data were analyzed using regression analysis. Findings: The results show that job commitment and job motivation positively affect OCB in Indonesia but not Malaysia. The results also reveal that job motivation affects OCB in both countries. In Indonesia, organizational culture and national culture partially moderate the influence of job commitment and motivation on OCB, except the commitment to the organization's culture. However, roles of these moderators in job commitment and motivation are not evident in Malaysia. The result of this study also shows that OCB affects performance in Malaysia but not Indonesia. Practical implications: The results of this study can be used to explore Indonesian and Malaysian employees. Although the culture of these two countries is originated from the same roots which cause many similarities among them, there are differences in terms of OCB and employee's performance that can affect organizational performance and also ways in dealing business with Indonesian and Malaysian companies. Originality/value: This study is one of the first studies to examine cross-cultural dimensions in two Southeast Asian countries. The findings contribute to the current OCB literature by confirming the roles of OCB and culture in the effects of job motivation and commitment on job performance.